Monitoring of spring barley varietal composition in the Rostov region - G. A. Filenko; N. A. Shmeleva; A. A. Dontsova; Yu. G. Skvortsova (Зерновое хозяйство России, 2025)
Spring barley, despite the decrease of sown areas, remains a significant grain food, feed and technical agricultural crop in the Don region. The purpose of the current study was to monitor spring barley varieties in the Rostov region. In order to solve this problem, there have been analyzed dynamics of sown areas, yields and spring barley varietal composition in six different soil and climatic zones of the region for the period from 2022 to 2024. There has been found that during this period, 27–30 spring barley varieties with different economic and biological characteristics are allowed for cultivation in the North Caucasus region. There has been established that over the past three years only 26–28 barley varieties have been cultivated on an area of 201.7 to 222.9 K hectares in the region. The largest areas under spring barley in the region are in such three main agroclimatic zones as northwestern, northeastern and southern (more than 60 %). The main scientific institutions producing seed material of spring barley varieties for the Rostov region are the FSBSI “ARC “Donskoy", the FSBSI “North Caucasian FSAC” and OOO “Agrostandart”. There has been determined that the maximum sowing area (155.5–168.1 K hectares) of spring barley for the period (2022–2024) was occupied by the varieties included in the register for more than 15 years. The most promising and productive varieties are ‘Prerie’, ‘Vakula’, ‘Ratnik’, ‘Leon’, ‘Gris’, ‘Odesskiy 22’, which are in demand in production regardless of the natural and climatic conditions of the Rostov region. The use of new and promising barley varieties included in the State List for the North Caucasus region will contribute to further productivity improvement and gross harvest increase of spring barley in the region.